2021
DOI: 10.3389/fncel.2021.682597
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factors in Parkinson’s Disease: Clinical Trials, Open Challenges and Nanoparticle-Mediated Delivery to the Brain

Abstract: Neurotrophic factors (NTFs) are small secreted proteins that support the development, maturation and survival of neurons. NTFs injected into the brain rescue and regenerate certain neuronal populations lost in neurodegenerative diseases, demonstrating the potential of NTFs to cure the diseases rather than simply alleviating the symptoms. NTFs (as the vast majority of molecules) do not pass through the blood–brain barrier (BBB) and therefore, are delivered directly into the brain of patients using costly and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 128 publications
0
33
0
Order By: Relevance
“…Compared to the plasmonic nanostructures summarized in Table S3, our SPIO-HGNS possess benefits, such as tunable SPR peak at the NIR region and functional sizes within 10-100 nm, which enable enhanced tumor uptake, efficient blood brain barrier crossing and deeper brain tissue penetration [54, 55, 56, 57]. We have also shown that Au coating displays excellent biocompatibility and efficient cellular uptake [8, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the plasmonic nanostructures summarized in Table S3, our SPIO-HGNS possess benefits, such as tunable SPR peak at the NIR region and functional sizes within 10-100 nm, which enable enhanced tumor uptake, efficient blood brain barrier crossing and deeper brain tissue penetration [54, 55, 56, 57]. We have also shown that Au coating displays excellent biocompatibility and efficient cellular uptake [8, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Variation in the pathological secretion of collagen VI also provides a plausible explanation as to why GDNF treatments appear more efficient in Hol Tg/Tg [BL6] mice compared to Hol Tg/Tg [FVB] mice. Indeed, the extracellular matrix is a major determinant of GDNF diffusion and activity [ 45 , 46 ]. Accordingly, levels of collagen VI in the diseased segment might affect both the distribution of rectally administered GDNF and the subsequent response of targeted ENS progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…NTFs are a group of neuropeptides (such as nerve growth factors) that support the development, maturation, and survival of neurons in the CNS. Nevertheless, NTFs prevent the loss of dopaminergic neurons and play a potential role in the treatment of PD [ 123 ]. However, the introduction of NTFs directly into the brain is limited, whether in terms of the cost issue, risky intracranial surgery, poor diffusion, and/or the failure to pass through the BBB.…”
Section: Types Of Brain Disordersmentioning
confidence: 99%